Perbaikan Profil Lipid pada Masyarakat Muslim Hiperlipidemia dengan Puasa Ramadhan di Denpasar Selatan - Ni Putu Juli Martasari; Dhiancinantyan Windydaca Brata Putri; I Gusti Lanang Made Rudiartha; Putu Yudhistira Budhi Setiawan (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Ramadan fasting is an activity to refrain from eating and drinking, which is very beneficial for health, one of which is in improving lipid profile levels that are disturbed or commonly called hyperlipidemia because fasting can reduce saturated fatty acid intake, increase fiber intake, reduce carbohydrate and alcohol intake. Hyperlipidemia is a lipid metabolism disorder characterized by an increase or decrease in lipid fraction levels in plasma such as an increase in total cholesterol, LDL, and triglyceride levels and a decrease in HDL levels. This study aims to determine the effect of Ramadan fasting on the lipid profile of hyperlipidemia patients in the Kepaon Islamic village community. This research is a quantitative study, with a pre-experimental research design using the One Group Pretest-Posttest model with purposive sampling taking. The examination includes total cholesterol, LDL, HDL, and triglycerides before and one month after fasting. The results of this study showed significant changes in the form of decreases in total cholesterol, triglycerides, and LDL levels with average values as follows 221.60±40.59 to 189.85±19.27; 149.65±66.07 to 103.10±43.96; and 153.20±34.23 to 116.60±18.91 with a p-value significance of 0.001. And there was an increase in HDL levels with an average value of 38.55±8.89 to 57.10±13.55 with a p-value significance of 0.001. This study can be concluded that Ramadan fasting decreases total cholesterol, triglycerides, and LDL levels and increases HDL levels.